STRUCTURAL CHARACTERISATION OF 5-HYDROXYTRYPTAMINE2A RECEPTOR IN HOMO SAPIENS BY IN - SILICO METHOD - Singh, Soni; Jha, Alok (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Structural characterization of 5-hydroxytryptamine (5-HT)2A receptor in homo sapiens using in silico method. Methods: In silico approach has particularly providing a realistic representation needed to understand the fundamental molecular structure of a serotonin receptor. The structure has been generated using Swiss model, Modeller 9.14, Phyre2, and Geno three-dimensional, which was visualized using PyMol, and validated by Procheck and ERRAT analysis along with the values of different secondary structures mapping to diverse sections of the Ramachandran plot. Results: We compared all different models. Further structural analysis suggested that the structure of 5-HT2A is a monomer with 18 alpha helices, seven beta sheets, and one disulfide bridge. There is no signal peptide region in the protein sequence. The structure contains mostly polar and aromatic amino acid as suggested by using hydropathy plot. However, in both partitioning systems bilayer to water and water to bilayer, there are some hydropathy predicted segments, which are also transmembrane segments. Finally, the pore features, including diameter profile, size, and shape, were determined by porewalker, and the shape of the pore was found to be UDSD. Conclusion: This study suggested that 5-HT2A receptor interaction with its natural ligand serotonin and other inhibitor compounds would further additional information about G protein-coupled receptors. The 5-HT2A receptor could be an important target for therapeutics development.